2012
DOI: 10.1177/230949901202000201
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tibial Bone Coverage of 6 Knee Prostheses: A Magnetic Resonance Imaging Study with Controlled Rotation

Abstract: The asymmetric tray provided improved tibial coverage at the expense of posterolateral and posteromedial overhang of the tibial tray.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 16 publications
2
43
1
Order By: Relevance
“…Increased Q-angle leads to lateral subluxation of patella, anterior knee pain and patellofemoral wear. 19,20 It has been observed that the best mediolateral or anteroposterior cortical fit of the tibial component in most cases does not result in optimal rotational alignment with the femoral component, 13 i.e. it leads to malrotation of tibial tray with respect to femoral component.…”
Section: Flexion Contracture In Degreesmentioning
confidence: 99%
See 4 more Smart Citations
“…Increased Q-angle leads to lateral subluxation of patella, anterior knee pain and patellofemoral wear. 19,20 It has been observed that the best mediolateral or anteroposterior cortical fit of the tibial component in most cases does not result in optimal rotational alignment with the femoral component, 13 i.e. it leads to malrotation of tibial tray with respect to femoral component.…”
Section: Flexion Contracture In Degreesmentioning
confidence: 99%
“…Also complete medial and lateral cortical coverage may lead to posterolateral or posteromedial overhang. 13 This posterolateral or posteromedial overhang can be reduced by internally rotating the tibial tray. But internal rotation of tibia increases the Q-angle and causes a mismatch between the femoral and tibial rotations.…”
Section: Flexion Contracture In Degreesmentioning
confidence: 99%
See 3 more Smart Citations